Dominant carpotarsal osteochondromatosis. Issue 8 (August 1993) - Maroteaux, P; Le Merrer, M; Bensahel, H; Freisinger, P
Abstract : Dominant carpotarsal osteochondromatosis is a particular disorder of the wrist and tibiotalar joints with abnormal bone proliferation and osteochondromas. Two patients, a mother and son, are described here; a similar condition has previously been described in seven affected members of a family. The upper and the lower limbs are affected in the same patient and the lesion can be bilateral. Autosomal dominant inheritance is a further criterion allowing the diagnosis of dysplasia epiphysealis hemimelica.